2014
DOI: 10.1021/jp509765a
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on Metalloporphyrin–Polyoxometalates Hybrid Complexes for Dye-Sensitized Solar Cells

Abstract: We use time-dependent density functional theory methods to discuss the absorption spectra, electronic transition properties, and photovoltaic performance of metalloporphyrin−polyoxometalates (POM) complexes for p-type dye-sensitized solar cells (DSSCs). The results show that the energy levels of the frontier molecular orbitals for dyes 2−6 match the requirements of p-type DSSCs. The absorption spectra of dyes 2−6 exhibit larger and broader absorptions compared to that of dye 1 by the introduction of POM. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Because of the popularity of the NiO metal oxide in many energy applications, more researches should be carried out to synthesize and characterize the polyoxonickelates that combine the virtues of nickel oxide and molecular design flexibility. Nevertheless, nickel species are found to be common ingredient in many polyoxometalates for cluster functionalization . For example, polynuclear nickel clusters with Ni 12 , Ni 13 , and Ni 25 cores has been incorporated in polyoxometalate to act as water oxidation catalysts whereas the photocatalysis of Ni 2+ and NiO is ruled out .…”
Section: Polyoxonickelatementioning
confidence: 99%
See 1 more Smart Citation
“…Because of the popularity of the NiO metal oxide in many energy applications, more researches should be carried out to synthesize and characterize the polyoxonickelates that combine the virtues of nickel oxide and molecular design flexibility. Nevertheless, nickel species are found to be common ingredient in many polyoxometalates for cluster functionalization . For example, polynuclear nickel clusters with Ni 12 , Ni 13 , and Ni 25 cores has been incorporated in polyoxometalate to act as water oxidation catalysts whereas the photocatalysis of Ni 2+ and NiO is ruled out .…”
Section: Polyoxonickelatementioning
confidence: 99%
“…Nevertheless, nickel species are found to be common ingredient in many polyoxometalates for cluster functionalization. 60,[150][151][152][153][154][155][156][157][158][159][160] For example, polynuclear nickel clusters with Ni 12 , Ni 13 , and Ni 25 cores has been incorporated in polyoxometalate to act as water oxidation catalysts whereas the photocatalysis of Ni 2+ and NiO is ruled out. 60 Ni 24 cages with calixarene and Pt clusters have been employed to activate the hydrogen evolution reaction.…”
Section: Polyoxonickelatementioning
confidence: 99%
“…However, the Hartree-Fock (HF) exchange function and the long-range function must be included to obtain more reasonable results. 48)/6-31G** level (LANL2DZ basis set for W, Co, Ni and Pd atoms) due to its efficiency and accuracy, 37,49,50 and PCM was employed in TDDFT calculations. The meta-GGA M06-2X functional 42 includes a high percentage of HF exchange has been proved to be a good method to calculate the rst hyperpolarizabilities.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In recent years, quantum chemistry method has become a reliable way to reveal the relationship between the structure and property of dyes, and it can provide a reliable theoretical basis for the rapid screening of high efficiency dye molecules [20][21][22][23][24][25][26][27][28][29][30][31][32]. Zhang et al [24] designed six dyes based on the POM conjugated zinc(II)-centered-porphyrin and investigated the absorption spectra, electronic transition properties, and photovoltaic performance of the six dyes for p-type dye-sensitized solar cells (DSSCs) by using time-dependent density functional theory methods.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [24] designed six dyes based on the POM conjugated zinc(II)-centered-porphyrin and investigated the absorption spectra, electronic transition properties, and photovoltaic performance of the six dyes for p-type dye-sensitized solar cells (DSSCs) by using time-dependent density functional theory methods. The results showed that the energy levels of the frontier molecular orbitals for dyes 2-6 matched the requirements of p-type DSSCs and the photovoltaic performances of dyes 2-6 were suitable for high-efficiency DSSCs.…”
Section: Introductionmentioning
confidence: 99%